Transmiáion efficiency of different non-persistent viruses infecting melon by four aphid species - Garzo, E.I.=700 1 Duque., M.; Fereres, A.
(Es, En)
ilus., 32 ref.
Keywords: APHIS; MYZUS PERSICAE; VIRUS; POTYVIRUS; TRANSMISION DE ENFERMEDADES; CUCUMIS MELO; ESPAÑA; PULGONES; CUCUMBER MOSAIC VIRUS; WATER MELON MOSAIC VIRUS; ZUCCHINI YSLLOW MOSAI VIRUS; VECTOR